Effect of Surfactants on Pressure-Sensitivity of CNT Filled Cement Mortar Composites - Han, Baoguo; Yu, Xun (Frontiers in Materials, 2014)
Sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (NaDDBS) were used as surfactants to disperse multi-walled carbon nanotubes (MWNT) in cement mortar and fabricate pressure-sensitive carbon nanotubes filled cement mortar composites. The pressure-sensitivity of cement mortar composites with different concentrations of MWNT and different surfactants was explored under repeated loading and impulsive loading, respectively. Experimental results indicate that the response of the electrical resistance of composites with NaDDBS to external force is more stable and sensitive than that of composites with SDS. Therefore, NaDDBS has higher efficiency than SDS for the dispersion of MWNT in cement mortar, and it is an effective surfactant for fabricating MWNT filled cement mortar composites with superior pressure-sensitivity.